THE ROLE OF MULTIPLIERS IN THE FORMATION AND IMPLEMENTATION OF REGIONAL INNOVATIVE DEVELOPMENT PROGRAMS - Kusmanovna Uandykova, Mafura; Igorevna Stepanova, Diana; Yevgenievna Shchepetova, Svetlana; Gheorghievna Zbrishchak, Svetlana (Revista Inclusiones, 2020)
Under current conditions, an important direction of ensuring innovative development and the task of implementing sustainable economic transformations associated with this process is the improvement of management tools, the development, implementation of new approaches and management criteria to achieve the necessary pace of innovative development of the country's economy.